2015
DOI: 10.1016/j.bbamcr.2014.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in peroxisome-deficient hepatocytes exhibit impaired respiration, depleted DNA, and PGC-1α independent proliferation

Abstract: The tight interrelationship between peroxisomes and mitochondria is illustrated by their cooperation in lipid metabolism, antiviral innate immunity and shared use of proteins executing organellar fission. In addition, we previously reported that disruption of peroxisome biogenesis in hepatocytes severely impacts on mitochondrial integrity, primarily damaging the inner membrane. Here we investigated the molecular impairments of the dysfunctional mitochondria in hepatocyte selective Pex5 knockout mice. First, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
85
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 75 publications
(21 reference statements)
6
85
1
Order By: Relevance
“…Importantly, as expression of catalase-SKL, a variant with enhanced peroxisome targeting efficiency, can repolarize mitochondria and reduce the number of senescent cells in late passage cell cultures of human fibroblasts (Koepke et al, 2007), it is reasonable to postulate that peroxisome-derived oxidative imbalance may rapidly impair mitochondrial function Walton and Pizzitelli, 2012). In support of this hypothesis are, among others, the findings that (i) inactivation of ABCD1, a peroxisomal VLCFA transporter causative for Xlinked adrenoleukodystrophy (X-ALD), causes oxidative damage to mitochondrial proteins and impairs oxidative phosphorylation (OXPHOS) in the spinal cord of mice (López-Erauskin et al, 2013), (ii) acute and chronic loss of PEX5 function quickly impair the activities of the RCCs I, III, and V in hepatocytes from mice (Peeters et al, 2015), and (iii) the activities of the muscle mitochondrial RCCs II, III, and IV are decreased in a Zellweger syndrome (ZS) patient with homozygous pathogenic mutations in the PEX16 gene (ZS is the most severe of the peroxisome biogenesis disorders) (Salpietro et al, 2015).…”
Section: Peroxisomes and Mitochondria Share An Intricate Redox-sensitmentioning
confidence: 62%
See 4 more Smart Citations
“…Importantly, as expression of catalase-SKL, a variant with enhanced peroxisome targeting efficiency, can repolarize mitochondria and reduce the number of senescent cells in late passage cell cultures of human fibroblasts (Koepke et al, 2007), it is reasonable to postulate that peroxisome-derived oxidative imbalance may rapidly impair mitochondrial function Walton and Pizzitelli, 2012). In support of this hypothesis are, among others, the findings that (i) inactivation of ABCD1, a peroxisomal VLCFA transporter causative for Xlinked adrenoleukodystrophy (X-ALD), causes oxidative damage to mitochondrial proteins and impairs oxidative phosphorylation (OXPHOS) in the spinal cord of mice (López-Erauskin et al, 2013), (ii) acute and chronic loss of PEX5 function quickly impair the activities of the RCCs I, III, and V in hepatocytes from mice (Peeters et al, 2015), and (iii) the activities of the muscle mitochondrial RCCs II, III, and IV are decreased in a Zellweger syndrome (ZS) patient with homozygous pathogenic mutations in the PEX16 gene (ZS is the most severe of the peroxisome biogenesis disorders) (Salpietro et al, 2015).…”
Section: Peroxisomes and Mitochondria Share An Intricate Redox-sensitmentioning
confidence: 62%
“…It should be noted, that loss of peroxisomal biogenesis and metabolism, a hallmark of Zellweger syndrome, is associated with impaired mitochondrial integrity. Recent studies in Zellweger-mouse models revealed impaired mitochondrial respiration, DNA depletion, PGC-1α independent proliferation of mitochondria and perturbed carbohydrate metabolism in peroxisome-deficient hepatocytes (Peeters et al, 2011(Peeters et al, , 2015. These findings suggest an impact on organelle interplay in Zellweger spectrum patients.…”
Section: Interplay Between Peroxisomes and Mitochondriamentioning
confidence: 83%
See 3 more Smart Citations